2017
DOI: 10.1039/c7ta03201c
|View full text |Cite
|
Sign up to set email alerts
|

MgFeSiO4 as a potential cathode material for magnesium batteries: ion diffusion rates and voltage trends

Abstract: Developing rechargeable magnesium batteries has become an area of growing interest as an alternative to lithium-ion batteries largely due to their potential to offer increased energy density from the divalent charge of the Mg ion. Unlike the lithium silicates for Li-ion batteries, MgFeSiO 4 can adopt the olivine structure as observed for LiFePO 4 . Here we combine advanced modelling techniques based on energy minimization, molecular dynamics (MD) and density functional theory to explore the Mg-ion conduction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 76 publications
1
37
0
Order By: Relevance
“…Olivine‐type MgMSiO 4 (M = Fe, Mn, Co, or Ni) possesses a high theoretical capacity and high theoretical redox potential, the presence of multivalent transition metals can reduce the damage to the structure during de‐intercalation of Mg 2+ ions. In view of the above advantages, a series of nanoparticles MgMnSiO 4 ( Figure 11 a), [ 58 ] Mg 1.03 Mn 0.97 SiO 4 , [ 59 ] MgFeSiO 4 [ 60,61 ] and 3D heterogeneous porous MgCoSiO 4 [ 62 ] with short solid‐phase diffusion distance as potential Mg storage cathode materials have been studied in recent years. Mesoporous Mg 1.03 Mn 0.97 SiO 4 cathode with carbon coating was synthesized using different techniques, their Mg storage capacities of nanosized Mg 1.03 Mn 0.97 SiO 4 could reach 64.5 mAh g −1 at 3.1 mA g −1 and 92.9 mAh g −1 at C/50 rate, respectively.…”
Section: Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Olivine‐type MgMSiO 4 (M = Fe, Mn, Co, or Ni) possesses a high theoretical capacity and high theoretical redox potential, the presence of multivalent transition metals can reduce the damage to the structure during de‐intercalation of Mg 2+ ions. In view of the above advantages, a series of nanoparticles MgMnSiO 4 ( Figure 11 a), [ 58 ] Mg 1.03 Mn 0.97 SiO 4 , [ 59 ] MgFeSiO 4 [ 60,61 ] and 3D heterogeneous porous MgCoSiO 4 [ 62 ] with short solid‐phase diffusion distance as potential Mg storage cathode materials have been studied in recent years. Mesoporous Mg 1.03 Mn 0.97 SiO 4 cathode with carbon coating was synthesized using different techniques, their Mg storage capacities of nanosized Mg 1.03 Mn 0.97 SiO 4 could reach 64.5 mAh g −1 at 3.1 mA g −1 and 92.9 mAh g −1 at C/50 rate, respectively.…”
Section: Cathodesmentioning
confidence: 99%
“…In other words, 2Li + extraction from Li 2 FeSiO 4 followed by Mg 2+ insertion, the obtained MgFeSiO 4 as RMBs cathode materials provided a capacity of more than 300 mAh g −1 with good retention upon cycling. [ 61 ] Furthermore, the potential pathway for Mg‐ion migration in MgFeSiO 4 structure was predicted by Islam's group using molecular dynamics (MD) and DFT (Figure 11c), [ 60 ] the lowest migration activation energy was 0.6 eV and a diffusion coefficient ( D Mg ) of 10 −9 cm 2 s −1 of MgFeSiO 4 was achieved. These works will provide a reference for optimizing the application of silicate electrodes in RMBs in the future.…”
Section: Cathodesmentioning
confidence: 99%
“…[ 92,93 ] Therefore, a series of olivine structure cathode materials have been reported for RMBs. Orikasa et al [ 94 ] presented ion‐exchange synthesized MgFeSiO 4 from Li 2 FeSiO 4 showed an attractive specific capacity over 300 mAh g −1 at a potential of 2.4 V. Heath et al [ 95 ] also used modeling techniques to systematically study the conduction of Mg 2+ . As shown in Figure 4 a, the Mg 2+ migration energy and diffusion coefficient ( D Mg ) of MgFeSiO 4 are 0.6 eV and 10 −9 cm 2 s −1 , respectively, which are favorable for Mg 2+ intercalation compared with other RMBs cathodes.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 95 ] Copyright 2017, The Royal Society of Chemistry. b) The hexagonal and monoclinic structure models of NASICON.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…This research also indicated that Small 2019, 15,1900105 Reproduced with permission. [86] Copyright 2017, The Royal Society of Chemistry.…”
Section: Olivine Structurementioning
confidence: 99%